2016
DOI: 10.1038/srep23917
|View full text |Cite
|
Sign up to set email alerts
|

A novel therapeutic strategy of lipidated promiscuous peptide against Mycobacterium tuberculosis by eliciting Th1 and Th17 immunity of host

Abstract: Regardless of the fact that potent drug-regimen is currently available, tuberculosis continues to kill 1.5 million people annually. Tuberculosis patients are not only inflicted by the trauma of disease but they also suffer from the harmful side-effects, immune suppression and drug resistance instigated by prolonged therapy. It is an exigency to introduce radical changes in the existing drug-regime and discover safer and better therapeutic measures. Hence, we designed a novel therapeutic strategy by reinforcing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…The decrease in IL-17A production, correlated with the exhaustion of T cells, may be due to the overexposure to Mtb antigens and hyperexpression of the exhausted marker programmed death-1 (PD-1). 12,13 Increased PD-1 expression appears to be relevant to the depressed production of IL-17A in TB because anti-PD-1 antibodies can enhance IL-17A production by Mtbstimulated CD4+ T cells of TB patients. 14 Anti-TB therapy can decrease PD-1 expression and increase IL-17A production by CD4+ T cells.…”
Section: Th17-related Cytokines/th17-like Cells and Their Roles In Mtmentioning
confidence: 99%
“…The decrease in IL-17A production, correlated with the exhaustion of T cells, may be due to the overexposure to Mtb antigens and hyperexpression of the exhausted marker programmed death-1 (PD-1). 12,13 Increased PD-1 expression appears to be relevant to the depressed production of IL-17A in TB because anti-PD-1 antibodies can enhance IL-17A production by Mtbstimulated CD4+ T cells of TB patients. 14 Anti-TB therapy can decrease PD-1 expression and increase IL-17A production by CD4+ T cells.…”
Section: Th17-related Cytokines/th17-like Cells and Their Roles In Mtmentioning
confidence: 99%
“…Although up‐regulated PD‐1 in active TB infection impedes T cell responses, blocking this PD1/PD‐Ls pathway can functionally rescue these T cells. Abs blocking PD‐1/PD‐Ls is able to enhance Ag‐specific IFN‐γ responses in cells from patients with TBP in vitro . We reported that PD‐1 was selectively up‐regulated by the activated CD4 + and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 91%
“…Abs blocking PD-1/PD-Ls is able to enhance Ag-specific IFN-responses in cells from patients with TBP in vitro. 17,26,27 We reported that PD-1 was selectively upregulated by the activated CD4 + and CD8 + T cells. Therefore, we 28,31 When transferred into uninfected animals, these cells persist, mount a robust recall response, and provide superior protection to M.tb re-challenge when compared to terminally differentiated Th1 cells that reside preferentially in the lung-associated vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that multifunctional cellular immune responses might be involved in the self‐cure process. Several studies have demonstrated the protective roles of host polyfunctional cells against numerous infectious organisms . For example, the frequency of Plasmodium falciparium ‐specific polyfunctional T cells has been associated with protection in humans .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the protective roles of host polyfunctional cells against numerous infectious organisms. [53][54][55][56][57] For example, the frequency of Plasmodium falciparium-specific polyfunctional T cells has been associated with protection in humans. 58 Similarly, the importance of durable polyfunctional viral antigen-specific protective T cell responses has also been demonstrated in HIV-infected rhesus macaques.…”
Section: Discussionmentioning
confidence: 99%